CAN ULTRASOUND IMAGING PREDICT THE DEVELOPMENT OF ACHILLES AND PATELLAR TENDINOPATHY? A SYSTEMATIC REVIEW AND META-ANALYSIS. Issue 4 (1st February 2017) - Auliffe, Sean Mc; Creesh, Karen Mc; O'Sullivan, Kieran; Purtill, Helen; Culloty, Fiona
Abstract : Background: Ultrasound [US] imaging is commonly used to visualise tendon structure. It is not clear whether the presence of structural abnormalities in asymptomatic tendons predicts the development of future tendon symptoms in the Achilles or patellar tendon. This led to considerable uncertainty in the management of sporting populations with a high prevalence of tendon related injuries. Objective: To investigate the ability of US imaging to predict future symptoms of patellar or Achilles tendinopathy. Design: A systematic review and meta-analysis. Setting: Prospective imaging in a range of clinical settings. Patients (or Participants): The majority of the participants involved athletic populations ranging from volleyball, basketball, soccer players, fencing, badminton, ballet dancing, running. Interventions (or Assessment of Risk Factors): Prospective studies that performed US imaging of Achilles OR patellar tendon structure among asymptomatic subjects at baseline and a clinical measure of pain and/or function at follow-up were included. Main Outcome Measurements: Tendon abnormalities were described as any deviation in tendon structure; e.g. hypoechogenicity, increased thickness, or increased vascularity as seen on power doppler US. Results: The majority of participants in the review were from sporting populations. Meta-analysis revealed tendon abnormalities on US are associated with future symptoms of both patellar and Achilles tendinopathy [RR =4.97, 95% CI: 3.20–7.73]. Subgroup analysis indicated tendon abnormalities at baseline were associated with an increased risk of both Achilles [RR=7.33, 95% CI: 2.95–18.24] and patellar [RR=4.35, 95% CI: 2.62–7.23] tendinopathy. Conclusions: This review indicates that tendon abnormalities US in asymptomatic tendons are predictive of future tendinopathy and are associated with at least a 4-fold increased risk. Identification of at risk athletes using screening tools such as US may allow preventative programs to be implemented. However, it is clear other factors beyond tissue structure are involved in the development of lower limb tendinopathy.